POLISI KEWANGAN MENURUT PERSPEKTIF EKONOMI ISLAM - Borhan, Joni Tamkin (Jurnal Syariah, 2019)
This anicle explains the role that monetary policy should be designed to play in an Islamic economy and to highlight how it can be made to play its role effectively if interest is abolished. This anicle also discussess the mechanism for equating the supply of money with its demand in the ab~ sence of interest as a regulating mechanism and the feasible alternatives to interest-bearing government securities for financing government budgetary deficits in a non-inflationary framework.